(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this the research work on measuring the In situ hydraulic conductivity by different techniques, measuring Ks at various depths by using various instruments, effect of land use land cover, hill slope etc., and estimation of Ks by using texture based equation. The hydraulic conductivity (KS) of soils is an important soil parameter that is essentially required for various fields of civil engineering where there is interaction between the soil and water such as estimation of seepage, drainage of fluid through the soil media, for groundwater supplies, settlement behaviour of structure, percolation and lateral flow of contaminants, checking the efficiency of compacted landfill liners, simulation of fluid flow through soil for modelling purpose, water and mass transport models and irrigation and drainage studies ,efficiency of domestic wastewater treatment system , reservoir characterization, leaching of pesticides from agricultural lands, and migration of pollutants from contaminated sites to the ground water. Stability of slopes in hilly areas will depend on the drainage of water through such soils which in turn depends on the hydraulic conductivity of soil. Soil saturated hydraulic conductivity (Ks) is a key variable in the water cycle. It co-determines how rainfall is partitioned into different water flow paths, such as groundwater recharge, lateral subsurface runoff and overland flow.